RAPID3 SCORE CAN PREDICT DISEASE ACTIVITY IN PRIMARY SJOGREN'S SYNDROME - Oz, B.; Karatas, A.; Omercikoglu, Z.; Catak, O.; Gozel, N.; Cur, S.; Koca, S. S. (Bmj Publishing Group, 2017)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 14-17, 2017 -- Madrid, SPAIN